SIRT1 As A Novel Therapeutic Target For Periodontitis: A Rapid Review - kuswandani, Faisal; Febriane Balafif, Felisha; Najmi, Nuroh; Rafisa, Anggun (Jurnal EduHealth, 2024)
SIRT1 plays a pivotal role in regulating a multitude of biological processes, including cellular metabolism, aging, DNA repair, inflammation, and oxidative stress. evidence suggesting a potential association between SIRT1 activity and periodontal health including periodontitis. This article aims to explore the immunobiological functions of SIRT1 in the initiation and progression of periodontitis. This comprehensive review utilized the PubMed and Cochrane Library databases to collate studies from December 2024 to December 2024. Arround 53 studies were screened and 5 studies were deemed suitable for analyses. Evidence based revealed that, SIRT1 levels elevated after periodontal treatment and its involvement in anti-inflammatory pathways suggest its beneficial role in managing periodontitis. Conclussion, clinical studies shows that SIRT1's potential as a biomarker and therapeutic target. Elevated SIRT1 levels after periodontal treatment and its involvement in anti-inflammatory pathways suggest its beneficial role in managing periodontitis. However, Prospective studies are necessary to deepen our understanding of their role in the pathophysiology of periodontitis and their potential clinical applications.